Trifluoroacetic Acid as an Effective Catalyst for Biginelli Reaction: One-Pot, Three-Component Synthesis of 3,4-Dihydropyrimidin-2(1H)-ones (and-Thiones) - Mohammad R. Mohammadizadeh; Neda Firoozi (E-Journal of Chemistry)
Trifluoroacetic acid (TFA) is introduced as an effective catalyst for promotion of Biginelli reaction. 3,4-Dihydropyrimidin-2(1H)-one (-thione) derivatives (DHPMs) were simply and efficiently prepared using TFA catalyzed one-pot, three-component condensation β-dicarbonyl compounds, aldehydes and urea (thio).